2013
DOI: 10.1097/psy.0b013e318274d30f
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Relationship of Depressive and Anxiety Symptoms With Dyslipidemia and Abdominal Obesity

Abstract: People with initially severe symptoms of depression or anxiety showed a subsequent decrease in HDL cholesterol levels and an increase in abdominal obesity over time, independent of a potential reduction in symptom severity in this period. Therefore, such people are at elongated and increasing risk for dyslipidemia and obesity, predisposing them to cardiovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
2
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 61 publications
5
66
2
2
Order By: Relevance
“…Several studies indicate that presence of depression or anxiety or more severe baseline levels of psychopathology are associated with poor metabolic outcomes over time, particularly obesity and dyslipidemia,6, 14 and sometimes over extended periods, up to 15 years later 59. Other studies indicate effects in the opposite direction 13, 60.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies indicate that presence of depression or anxiety or more severe baseline levels of psychopathology are associated with poor metabolic outcomes over time, particularly obesity and dyslipidemia,6, 14 and sometimes over extended periods, up to 15 years later 59. Other studies indicate effects in the opposite direction 13, 60.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, most of the current evidence involves depressive symptoms, whereas associations for anxiety symptoms or diagnosis of depression and anxiety have been infrequently reported, and results have been inconsistent 13, 14, 15. Consequently, it remains unclear as to whether, over time, psychopathology impairs components of the metabolic syndrome, or vice versa.…”
Section: Introductionmentioning
confidence: 99%
“…Three studies have reported on the prospective relationship between anxiety and later weight gain, with two finding associations between baseline anxiety and increased weight at 2-year follow-up. In one of these studies, this relationship was not moderated by sex and was no longer significant for either men or women after controlling for depression [22]. In the other study, the pattern of results by sex changed after adjusting for baseline depression and physical activity.…”
Section: Long-term Studies (>5 Years)mentioning
confidence: 93%
“…More specifically, a bidirectional association was found between depression and obesity with obesity increasing the risk of depression and prior depression increasing the likelihood of obesity. Several studies have found that abdominal obesity in particular may be characteristic of depression (Carpiniello et al, 2012, Rivenes et al, 2009, van Reedt Dortland et al, 2013.…”
Section: Is There An Association Between Obesity and Psychiatry Disormentioning
confidence: 99%